Early postoperative seizures in liver and kidney recipients - O. M. Tsirulnikova; A. V. Syrkina; I. A. Miloserdov; I. E. Pashkova; S. Yu. Oleshkevich; I. B. Komarova (Вестник трансплантологии и искусственных органов)
Background. Transplantation is presently the only treatment for end-stage liver and kidney failure. Up to 42% of liver transplant recipients and up to 30% of kidney transplant recipients have neurological complications from the transplantation. Acute symptomatic seizures (ACS) occupy an important place in the structure of early postoperative neurological complications. Verification of the causes of seizures and management of the risk of relapse is presently a critical task.Objective: to review recent advances in ACS assessment, prevalence, and treatment approaches in liver and kidney transplant recipients.Materials and methods. The causes of ACS after liver and kidney transplant are diverse. Nonspecific causes of seizures such as dysmetabolic and volemic changes associated with transplantation are widely known. There are also specific syndromes associated with seizures in liver and kidney recipients, such as posterior reversible leukoencephalopathy syndrome, neurotoxicity of calcineurin inhibitors, hyponatremia in the final stage of liver failure, hypocalcemia in kidney recipients, etc. Diagnosis is made based on general rules, and treatment depends on the identified causes of seizures. Management of acute symptomatic seizures involves prescribing anticonvulsants according to the risk of seizure recurrence; immunosuppression is converted when neurotoxicity is identified. Results. The diagnostic algorithm, and often the treatment strategies, in ACS cases in liver and kidney recipients, are not clearly defined.Conclusion. Due to the multiple causes of ACS, there are differences in treatment tactics. Further accumulation and generalization of ACS outcome data will help in creating a convenient algorithm for rapid identification of the cause and the most effective treatment tactics.